If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -3x = kx Solving 8 + -3x = kx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1kx' to each side of the equation. 8 + -1kx + -3x = kx + -1kx Combine like terms: kx + -1kx = 0 8 + -1kx + -3x = 0 Add '-8' to each side of the equation. 8 + -1kx + -8 + -3x = 0 + -8 Reorder the terms: 8 + -8 + -1kx + -3x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1kx + -3x = 0 + -8 -1kx + -3x = 0 + -8 Combine like terms: 0 + -8 = -8 -1kx + -3x = -8 Reorder the terms: 8 + -1kx + -3x = -8 + 8 Combine like terms: -8 + 8 = 0 8 + -1kx + -3x = 0 The solution to this equation could not be determined.
| -4(1+3)=-4*1+(-4)*3 | | 5(-3x+8)=40-15x | | 3y^2-10=20 | | 3(4x-2)-3=12x-9 | | 5x+4=7(x-3)+17 | | 2x^2+2x-5=0 | | t+0.23=56 | | 2+13=17 | | 35=70-7x | | 5(-3x+8)= | | 3*7=7*3 | | sqrt(7x-6)-2=3x-24 | | 6(a+5)=5(a+6)-6 | | y=11x+9 | | (x-1)+31=4x | | 78-29n=4n-35n | | y=-1.5x+8 | | -6(x+3)+90=3x-9(x-6) | | w^2-6w-64=0 | | 4(n+14)-3=292 | | 66=3y-17 | | 2a+44+(a+10)=180 | | 10(z+1)-4(z-1)=2(z-2)+3(z-3) | | 27x+4=18x+1 | | 10(z+1)-4(z-1)=2(z-2)+(z-3) | | 10-3x=24+4x | | 13(3x-5)=6x-4 | | 20+r=r-2(3r+3) | | 5a-b=1 | | K-e=m | | 7x+7=121 | | 3n-4=45 |